Effect of Fiber Resin Coating and Occlusal Preparation Thickness of Endocrown Restoration - Jeffrey Dwijayana Susanto; Ade Prijanti Dwisaptarini; Selviana Wulansari; Janti Sudiono; Moehamad Orliando Roeslan (Scientific Dental Journal, 2024)
Background: Teeth rehabilitation after root canal treatment with extensive crown loss is a challenge for clinicians. Endocrown restorations are indicated for cases of extensive loss of crown structure, in conditions where the use of posts does not possible. The use of fiber resin coating acts as a stress breaker and absorption on the dentin thereby increasing fracture resistance. Aim: To determine the effect of fiber resin coating as core build up material and occlusal preparations thickness on fracture resistance of endocrown restorations. Methods: An experimental study was conducted on 20 extracted molars and root canal treatment was performed. The samples were divided into four groups, which consist of with and without fiber resin coating, and with a different composite resin endocrown thickness. Fracture resistances were tested on the samples using a universal testing machine. Results: One-way ANOVA test showed a significant difference in fracture resistance value (p>0.05) between the tested groups. Tukey’s post hoc test results showed significant differences in all groups except for the thickness of 3.5 mm and 2 mm groups with FRC. Conclusion: There was a significant difference in fracture resistance between composite resin endocrown restorations with different thickness, either without fiber reinforced composite or using fiber reinforced composite as the core build up material.